PERAN LATIHAN FISIK DALAM PENANGANAN OBESITAS: AKSI IRISIN PADA PROSES PENCOKELATAN - Dewi Irawati Soeria Santoso; Imelda Rosalyn Sianipar; Neng Tine Kartinah (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2020)
In recent years, the prevalence of obesity continues to increase, leading to a public health problem. Therefore, the obesity problem needs serious attention and treatment approaches. Exercise is one of the treatment approach to combat obesity because exercise plays a role in beiging/browning process. Beiging is a differentiation process from white adipocyte to beige adipocyte, which has similar characteristics to brown adipocyte and is marked with an increase of UCP-1 expression. Irisin plays a role in increasing UCP-1 expression by activating p38 mitogen-activated protein kinase (MAPK) and extracellular-signal regulated kinase (ERK) signaling. Muscle contraction during exercise can activate PGC-1α, which leads to the synthesis of irisin. Exercise may increase irisin levels in skeletal muscle and consequently, play as a mediator of beiging process in adipose tissue.